Effectiveness of a Crocus sativus Extract on Burn Wounds in Rats - Alemzadeh, Esmat; Oryan, Ahmad (Planta Medica, 2018)
Crocus sativus is a spice with various pharmacological properties. Crocin, picrocrocin, and safranal are the main compositions of saffron that have recently been considered in the therapy of many diseases. High-performance liquid chromatography analysis revealed presence of these compounds in our saffron extract. This study was carried out to evaluate the effect of saffron on burn wound healing at an in vivo model. Saffron was topically applied on burn wounds in rats; the percentage of wound closure, wound contraction, and the levels of main cytokines and growth factors were measured. The saffron extract was also applied to evaluate the proliferation and migration of human dermal fibroblast (HDF) cells using in vitro scratch assay and resulted in active proliferation and migration of the HDF cells in a dose-dependent manner. A clear enhanced healing was observed in the saffron-treated wounds compared to the silver sulfadiazine and negative control groups. Decreased expression of interleukin-1β and transforming growth factor-β1 (TGF-β1) during the inflammatory phase demonstrated the role of saffron in promoting wound healing. In addition, enhanced TGF-β1 expression during the proliferative phase and basic fibroblast growth factor during the remodeling phase represented regenerative and anti-scarring role of saffron, respectively. Our histological and biochemical findings also confirmed that saffron significantly stimulated burn wound healing by modulating healing phases. Therefore, saffron can be an optimal option in promoting skin repair and regeneration. Application of this herbal medicinal drug should be encouraged because of its availability and negligible side effects.
Keywords: Crocus sativus; Iridaceae; interleukin-1β; wound healing; scratch assay